Determinants of Anemia Among Adolescent Girls: A Systematic Literature Review - Lubis, Mifthah Muliani; Azzahra, Shzalfa; Apriningsih, Apriningsih (Jurnal Kesmas Jambi, 2026)
Anemia is common among adolescents, especially girls who have begun menstruating, and is associated with reduced immunity, physical activity, academic performance, and fitness, as well as increased risks of low birth weight and maternal–neonatal mortality if it continues into pregnancy. This study aimed to summarize factors influencing anemia among adolescent girls based on recent evidence. A literature review was conducted using Google Scholar, PubMed, and Scopus to identify primary full-text articles in Indonesian or English published between 2021 and 2025 with the keyword “anemia in adolescent girls.” Anemia in adolescent girls is associated with nutritional status, menstrual cycle patterns, dietary habits, knowledge level, socioeconomic conditions, maternal education, adherence to iron tablet consumption, and physical activity. Anemia in adolescent girls is a multifactorial problem, requiring integrated prevention strategies that address nutrition, health behavior, and social determinants.